Perception, career choice and self-efficacy of UK medical students and junior doctors in urology - Jones, Patrick; Rai, Bhavan Prasad; Qazi, Hasan A.R.; Somani, Bhaskar K.; Nabi, Ghulam (Canadian Urological Association Journal, 2015)
Introduction: There is a growing concern about the reduced clinical exposure to urology at undergraduate level in the United Kingdom. As a consequence, the competencies of junior doctors are considered inadequate. The views of these doctors in training towards urology remain under reported. Methods: A modified Delphi method was employed to construct a questionnaire. Given the rise of social media as a platform for scientific discussion, participants were recruited via a social networking site. Outcomes assessed included career preference, exposure to urology, perceived male dominance, and confidence at core procedures. Results: In total, 412 and 66 responses were collected from medical students and junior doctors, respectively. Overall, 41% of participants felt that they had received a good level of clinical exposure to urology as part of their training and 15% were considering a career in this speciality. Female students were significantly less likely to consider urology as a career option (p < 0.01). Of these, 37% of the students felt confident at male catheterization and 46% of students regarded urology as a male-dominated speciality. Conclusions: Urology is perceived as male dominated and is the least likely surgical speciality to be pursued as a career option according to our survey. Increased exposure to urology at the undergraduate level and dedicated workshops for core urological procedures are needed to address these challenges.